LEGITIMACY OF ADVOCATES RELATED TO THE COURT EXAMINATION PROCESS - Muhammad Rezeqi; Zenny Rezania Dewantary (President University, 2018)
Court examination in Indonesia, particularly on the first and second stage, works on examining facts of a disputed case. Ideally, the Judge’s decision is made based on consideration about the case. However, one case showed that the legitimacy of the advocate team that worked on that case, interfere the Judge consideration and changed the result of the examination. The problem was, the presumed illegitimate advocate was made based on a vast-changing law about advocate. Indonesia experienced several change from multi-bar to single-bar and to multi-bar system of advocate bar. The question of the legitimacy of the advocate on that case was based on that unfortunate condition of the bar system, not because of the neglect performed by the advocates themselves. This led to a question on how the procedural aspect like the legitimacy of advocate could affect the material aspect, which is the on-going case and resulted to a different verdict.